Prevalence of transmitted drug resistance and impact of transmitted resistance on treatment success in the German HIV-1 Seroconverter Cohort. - Barbara Bartmeyer (Public Library of Science (PLoS), 2010)
Background The aim of this study is to analyse the prevalence of transmitted drug resistance, TDR, and the impact of TDR on treatment success in the German HIV-1 Seroconverter Cohort. Methods Genotypic resistance analysis was performed in treatment-naïve study patients whose sample was available 1,312/1,564 (83.9% October 2008). A genotypic resistance result was obtained for 1,276/1,312 (97.3%). The resistance associated mutations were identified according to the surveillance drug resistance mutations list recommended for drug-naïve patients. Treatment success was determined as viral suppression below 500 copies/ml. Results Prevalence of TDR was stable at a high level between 1996 and 2007 in the German HIV-1 Seroconverter Cohort (N = 158/1,276; 12.4%; CI(wilson) 10.7-14.3; p(for trend) = 0.25). NRTI resistance was predominant (7.5%) but decreased significantly over time (CI(Wilson): 6.2-9.1, p(for trend) = 0.02). NNRTI resistance tended to increase over time (NNRTI: 3.5%; CI(Wilson): 2.6-4.6; p(for trend)= 0.07), whereas PI resistance remained stable (PI: 3.0%; CI(Wilson): 2.1-4.0; p(for trend) = 0.24). Resistance to all drug classes was frequently caused by singleton resistance mutations (NRTI 55.6%, PI 68.4%, NNRTI 99.1%). The majority of NRTI-resistant strains (79.8%) carried resistance-associated mutations selected by the thymidine analogues zidovudine and stavudine. Preferably 2NRTI/1PIr combinations were prescribed as first line regimen in patients with resistant HIV as well as in patients with susceptible strains (susceptible 45.3%; 173/382 vs. resistant 65.5%; 40/61). The majority of patients in both groups were treated successfully within the first year after ART-initiation (susceptible: 89.9%; 62/69; resistant: 7/9; 77.8%). Conclusion Overall prevalence of TDR remained stable at a high level but trends of resistance against drug classes differed over time. The significant decrease of NRTI-resistance in patients newly infected with HIV might be related to the introduction of novel antiretroviral drugs and a wider use of genotypic resistance analysis prior to treatment initiation.